FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KARYAWAN PADA PT. FEDERAL INTERNASIONAL FINANCE BATAM - Ester Jenny Kristina Siahaan; Hikmah Hikmah (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
During 2021 PT. Federal International Finance Batam only realized 89.89% of its performance target, so it became a problem because the target was not met 100%. This uncertainty is thought to be due to various things such as motivation, work stress, and work. The purpose of this study is to find out how the influence of motivation, work stress and work discipline on the performance of employees of PT. Federal International Finance Batam either partially or simultaneously. This research is quantitative by determining the sample using slovin, the sampling technique used is probability sampling with primary data sources obtained through questionnaires. The sample used was 115 employee respondents. The results of the study partially show that motivation has a significant effect on employee performance with a ttable value (3.316 > 1.974) and a significance value of (0.001 < 0.05), work stress has no significant effect on employee performance with a t table value (-1.752 < 1.974) and a significance value of (0.082 > 0.05), work discipline has a significant effect on employee performance with the table (0.557 > 1.974) and a significance value of (0.009 < 0.05), simultaneously motivation, work stress and work discipline affect employee performance with a value of f table (8,842 > 3.05) and a significance value of (0.000 < 0.05). The conclusion according to the hypothesis is that partially motivation has a significant effect on the performance of employees of PT. Federal International Finance Batam or H1 is accepted, work stress has no significant effect on the performance of PT. Federal International Finance Batam or H2 is rejected, work discipline has a significant effect on the performance of PT. Federal International Finance Batam or H3 received simultaneously, work stress and work discipline affect the performance of employees of PT. Federal International Finance Batam or H4 is accepted.